The impact of male infertility faculty on urology residency training. (11th May 2022) - Asanad, Kian; Nusbaum, David; Fuchs, Gerhard; Rodman, John C. S.; Samplaski, Mary K.
Abstract: The objective of this study was to determine the impact of having male infertility on urology residents' infertility training experience, surgical confidence, and In‐Service‐Exam Infertility/Sexual Medicine subscores. We electronically surveyed urology residents throughout the United States querying exposure to infertility faculty and fertility knowledge. Univariable and multivariable analysis was performed to determine predictors of higher In‐Service Exam Infertility/Sexual Medicine sub‐scores and self‐rated infertility competency. Fifty‐four of 72 respondents (75%) reported that male infertility comprises ≤10% of their training. Of the 63 residents who have a reproductive urologist on faculty, 66.7%, 47.6%, and 49.2% have scrubbed/observed a microsurgical varicocelectomy, vasectomy reversal and testicular sperm extraction, respectively. Residents exposed to infertility faculty are more likely to self‐rate their infertility understanding as "excellent" or "good" ( p = 0.04 and p = 0.02, respectively), and 14.4× more likely to feel confident performing infertility procedures, versus residents lacking faculty ( p < 0.001). Residents having formal microsurgical training have better self‐rated infertility understanding ( p < 0.001), non‐obstructive azoospermia management ( p = 0.01), and competency performing infertility procedures ( p < 0.001). Residents exposed to fertility faculty are more likely to feel confident performing fertility procedures after residency ( p = 0.001). In conclusion, infertility comprises a minority of residency training. Most residents anticipate performing infertility procedures in practice, despite two‐thirds lacking confidence performing these. Having an infertility faculty and formal microsurgical training improves residents' surgical confidence, non‐obstructive azoospermia management, and global male infertility understanding. A structured educational curriculum may improve resident infertility training.